Postoperative creatine kinase elevation following hip arthroscopy and associated risk factors - Hisahiro Tonotsuka; Hajime Sugiyama; Daisuke Tanaka; Tatsuto Ito; Ayano Amagami; Keishi Marumo (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of this study was to investigate postoperative CK and risk factors for CK elevation after hip arthroscopy. Methods: This retrospective study reviewed 122 patients (50 males, 72 females; mean age, 44.1 years) who underwent hip arthroscopy from September 2012 to March 2018. For all patients, CK was investigated preoperatively, on postoperative days 1 and 3, and at postoperative weeks 1 and 2. Univariate and multivariate analysis was performed for parameters including sex, age, body mass index, preoperative glomerular filtration rate, diagnosis, duration of surgery, and duration of traction to determine the risk factors for CK > 10 upper limit of normal (CK > 10 ULN; 1900 IU/L for males and 1500 IU/L for females) after surgery. Results: Mean CK was 104.7 ± 68.7 IU/L preoperatively and 839.2 ± 2214.0, 523.9 ± 1449.4, 186.0 ± 690.7, and 122.0 ± 307.1 IU/L on postoperative days 1 and 3 and at postoperative weeks 1 and 2, respectively. CK was significantly higher on postoperative days 1 and 3 than before surgery. In total, 11 patients (9.0%), including 8 males (16.0%) and 3 females (4.2%), had CK > 10 ULN. Younger age and longer duration of traction are independent risk factors for CK > 10 ULN. Conclusion: After hip arthroscopy, CK levels should be monitored, especially in young patients and cases of prolonged duration of traction during surgery. Level of evidence: Level IV, therapeutic study. Keywords: Hip arthroscopy, Arthroscopic surgery, Creatine kinase, Rhabdomyolysis, Complication